An investigation of the leadership practices and organizational culture at a private Christian school - Babu, Bithun (Rhodes University, Faculty of Commerce, Rhodes Business School, 2018)
The purpose of this study is to investigate the leadership practices and organizational culture at a private Christian school in the Eastern Cape. A preliminary review of leadership literature suggested that traces of servant leadership may be apparent at the organization. Thus servant leadership will form a key focus area for exploration in this study. An analysis of this nature can make one aware of the influence leadership has in shaping the organizational culture of an institution. This in turn can be used to inform the future thinking around leadership efforts with respect to culture formation within an organization. The issue was addressed by consulting various articles to view the issue from different perspectives. The school served as a vehicle to explore the tenets of leadership and organizational culture. The study will take the form of a descriptive quantitative study. It was concluded that leadership plays a significant role in establishing the culture at an organization. However, leadership is not the only factor that shapes the organizational culture of an institution. The beliefs and values of the organization also has a role in shaping the overall culture and identity of an organization.
Keywords: Church schools -- South Africa -- Eastern Cape; Leadership; Corporate culture